Jakarta governor’s election : implications for 2014 - Yoes, C. Kenawas (2012)
The outsider pair of Joko Widodo-Basuki Tjahaja Purnama garnered an unexpected margin of almost eight percent in defeating the incumbent Fauzi Bowo-Nachrowi Ramli in the Jakarta gubernatorial election on 20 September 2012. There are several observable implications for the 2014 presidential elections in Indonesia.